Efektivitas Kurikulum Terpadu Islam-Sains dalam Meningkatkan Kompetensi Global Siswa di Berbagai Konteks Regional - Aisah Aisah; Mappanyompa Mappanyompa; Mustapa Ali (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This study aims to measure in depth the effectiveness of implementing an integrated curriculum that integrates Islamic values and science in improving students' global competence at the regional level. Using a quantitative approach through a survey, this study involved 102 respondents consisting of male and female students. The research instrument was a Likert scale questionnaire that was prepared based on relevant global competence indicators. Data analysis using multiple linear regression was conducted in two stages to test the effect of independent variables on the dependent variable. The results of the first stage of analysis showed that the integrated curriculum contributed 31.4% to the improvement of students' global competence. This indicates a positive relationship between the implementation of an integrated curriculum and students' ability to adapt to the demands of an increasingly complex global world. In the second stage, by adding control variables, the R-square value increased to 35.4%, reinforcing the previous finding that the integrated curriculum has a significant influence on the development of students' global competence. The findings of this study provide important implications for the development of educational policies at the regional level. An integrated curriculum that integrates Islamic values and science is proven to be effective in improving students' ability to face global challenges. Therefore, it is recommended to expand the implementation of this integrated curriculum in more schools and conduct further research to identify other factors that may affect the effectiveness of the curriculum implementation.